Adapting Financial Management Strategies Amidst Economic Turmoil: A Case Study of Gama Corporate's Liquidity and Restructuring Initiative - Irwan Moridu; Zainal Abidin (Eastasouth Institute, 2023)
In an era of economic turbulence, organizations face the imperative to adapt their financial management strategies to navigate the uncertain terrain. This research presents a case study of Gama Corporate, a leading financial institution, and examines the liquidity and restructuring initiatives undertaken amidst economic turmoil. Through a qualitative case study approach, involving documentary analysis, semi-structured interviews, and surveys, this research explores the drivers, strategies, outcomes, and lessons learned from Gama Corporate's experience. The results revealed that external economic turmoil, compounded by internal challenges, served as a catalyst for Gama Corporate's liquidity and restructuring initiatives. The company implemented a multifaceted approach, which included liquidity management and strategic restructuring. In the short term, the initiative incurred costs, including staff reductions and one-off losses, but in the long term, it resulted in greater financial stability and sustainable profitability. The lessons learned from this case underscore the importance of proactive liquidity management, the need for strategic restructuring when faced with financial challenges, and the importance of transparent communication with stakeholders. The findings from this study contribute to a broader understanding of financial management strategies during times of economic hardship, emphasizing the role of adaptation, innovation, and resource utilization in achieving financial resilience. The insights gained offer practical guidance for organizations looking to improve their financial strategies in a volatile economic landscape.